2004
DOI: 10.1002/ps.906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and phloem mobility of acidic derivatives of the fungicide fenpiclonil

Abstract: A series of derivatives of the phenylpyrrole fungicide fenpiclonil was synthesized in which a carboxyl group was present at various sites of this non-phloem-mobile molecule. Using the Kleier model, all these acidic analogues were predicted to be moderately phloem-mobile, especially the N-substituted derivatives. One of these latter molecules, N-carboxymethyl-3-cyano-4-(2,3-dichlorophenyl)pyrrole, exhibited some fungicidal activity on the pathogenic fungus Eutypa lata, and was then tested as a phloem-mobile pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 22 publications
2
79
0
Order By: Relevance
“…6A). These values were lower than those noted (21-or 22-fold) for Suc and Phe, which are taken up by specific carrier systems (Lemoine, 2000;Chen et al, 2001), much higher than those reported (0.2-or 0.3-fold) for glyphosate (Delétage-Grandon et al, 2001) and acidic derivatives of fenpiclonil (Chollet et al, 2004(Chollet et al, , 2005, but close to that noted for 2,4-D, which is less ionized than SA at apoplastic pH (Fig. 6B) but larger in size (Fig.…”
Section: Measurement Of Sa Accumulation In the Phloem Sap And Comparisupporting
confidence: 49%
See 2 more Smart Citations
“…6A). These values were lower than those noted (21-or 22-fold) for Suc and Phe, which are taken up by specific carrier systems (Lemoine, 2000;Chen et al, 2001), much higher than those reported (0.2-or 0.3-fold) for glyphosate (Delétage-Grandon et al, 2001) and acidic derivatives of fenpiclonil (Chollet et al, 2004(Chollet et al, , 2005, but close to that noted for 2,4-D, which is less ionized than SA at apoplastic pH (Fig. 6B) but larger in size (Fig.…”
Section: Measurement Of Sa Accumulation In the Phloem Sap And Comparisupporting
confidence: 49%
“…The discrepancy between SA uptake and percentage of the undissociated form of the molecule at biological pH is still more marked when a homogeneous aqueous medium is taken into consideration (pK a 3.0). By contrast, data from systemicity tests using the Ricinus system indicate that acidic derivatives of the fungicide fenpiclonil (compounds 2a and 2b) are taken up only in their undissociated form in accordance with the iontrap mechanism (Chollet et al, 2004(Chollet et al, , 2005.…”
Section: Time-course Experimentsmentioning
confidence: 88%
See 1 more Smart Citation
“…A residual uptake of BA and SA at pH values close to neutrality was also noted in intestinal cells Tsuji et al, 1994). By contrast, phloem uptake of acid derivatives of fenpiclonil in Ricinus occurred only in their permeant undissociated form (Chollet et al, 2004(Chollet et al, , 2005.…”
Section: Structure-phloem Mobility Relationshipsmentioning
confidence: 82%
“…The algorithms for the predictions are based on contributions of separate atoms, structural fragments, and intramolecular interactions between different fragments. LogD is a very important parameter for bioavailability and absorption studies of drugs (van de Waterbeemd et al, 2003) and agrochemicals (Chollet et al, 2004(Chollet et al, , 2005. The calculation of confidence limits for LogD (d LogD) is not implemented into ACD software but can be evaluated for a monoacid with the following formula: where logP is the octanol-water partition coefficient for uncharged species and logPion is the octanol-water partition coefficient for negatively charged species.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%